Penetapan Anggaran Pendapatan Belanja Daerah Dengan Peraturan Kepala Daerah - Sutiyoso Sutiyoso; Iwan Rachmad Soetijono; RA. Rini Anggraeni (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The regional budget or APBD is the main policy instrument for regional governments, occupying a central position in efforts to develop the capabilities and effectiveness of regional governments. The regional budget should be used as a tool for determining the amount of income and expenditure, a tool for decision making and distribution planning as well as a tool for authorizing future expenditure and a standard measure for assessing performance as well as a coordination tool for all activities in various work units. Minister of Home Affairs Regulation No. 3 of 2006 has provided time limits for each stage in preparing the APBD. In reality, it is not uncommon for local governments to be unable to meet these time limits. Delays in enacting Regional Budget Regulations result in delays in submitting APBD data. Regions that are late in submitting APBD data will be given sanctions in the form of delays in the distribution of balancing funds, and this delay can eliminate the opportunity for regions to obtain regional incentive funds.